Leveraging Packet Tracer as a common assessment tool in a virtual learning environment: a case study / Zarina Zainol ... [et al.] - Zainol, Zarina; Ahmad, Siti Arpah; Mohd Fuzi, Mohd Faris; Harun, Nurzalina; Mazlan, Mazwani Ayu (UiTM Press, 2024)
Virtual learning environment is a must for remote learning. Nowadays with the COVID-19 pandemic, the education paradigm has shifted to adopt distance learning approaches, thus, a virtual learning environment is preferred as a learning platform. Assessment is one of the important parts of the learning process. This study shares the experience of adopting Packet Tracer (PT) as a common assessment tool for computer networking subjects, namely Routing and Switching Technologies (ITT532). This course is a skill-based subject that ideally teaches face-to-face. However, due to COVID-19, remote learning was adopted. PT is a skill-based assessment that focuses on configurations of network devices to simulate network scenarios and environments. By leveraging the Learning Management System (LMS), specifically uFuture, PT has been employed to execute skill-based evaluation. Several network configurations such as VLAN, trunking, Inter-VLAN routing, port security, and static routing (IPV4) are discussed in this study case.